Efektivitas Komunitas Belajar dalam Meningkatkan Kualitas Guru di Sekolah - Supardi U.S.; Henhen Herdiana (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Teacher learning communities are regarded as essential means to improve education quality through collaboration and professional development. However, implementation within formal school contexts faces challenges, such as time constraints, limited structural support, and low awareness of the benefits of learning communities. This study aims to explore the effectiveness of learning communities in enhancing teacher quality in schools and to identify factors influencing teacher participation. The research method employed is a literature review, encompassing analysis of 25 articles from various relevant academic journals. Thematic analysis highlights key topics, including effectiveness, challenges, and opportunities for the development of learning communities. Findings indicate that learning communities have a positive role in enhancing teacher competence and work motivation. However, significant obstacles remain, such as lack of support from school management and limited understanding. The study also emphasizes the potential for digital technology-based learning communities, which could increase teacher participation by providing more flexible access. This study concludes that stronger policy support and further research are needed to address implementation barriers and maximize the potential of learning communities to enhance teaching quality in schools.